Synthesis, characterisation and assessment of antimicrobial activity of doped zinc oxide nanoparticles against selected waterborne pathogens - Volofu, Nomasamariya Elsie (Vaal University of Technology, 2019)
The aim of the study is to synthesise, characterize and assess the antimicrobial activity of cobalt oxide, zinc oxide and cobalt-doped zinc oxide nanoparticles against selected waterborne pathogenic fungi (yeasts and moulds) and bacteria. Various types of oxide based nanomaterial are an attractive option for the disinfection of water due to its high chemical stability and non-toxicity towards human cells. Synthesis of Co -doped ZnO and Co3O4nanoparticles was done through mechanochemical synthesis and urea based synthesis and microwave heating was employed for the preparation of ZnO nanoparticles. The ZnO nanoparticles were produced in short reaction and it was white color. Cobalt oxide (Co3O4) nanoparticles appeared as a pink precipitate but was turned black after being calcined. The synthesis of Co- ZnO nanoparticles was successfully prepared and blue solid was obtained from pink cobalt ion solution. The nanoparticles were characterised by X- Ray Diffraction (XRD), Fourier Infrared Spectroscopy (FTIR), UV–visible spectroscopy, Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) (Yang et al. 2003). In this research project, the antibacterial activities of NPs were carried out by well diffusion method and minimum inhibitory concentration (MIC). MIC is the lowest concentration of a chemical, usually a drug, which prevents visible growth of bacterium. Bacterial strains used in the study are: Salmonella enterica, Escherichia coli, Shigella sonnei and Staphylococcus aureus, yeast and mould is: Candida albicans and Aspergillus niger. The antimicrobial results obtained showed that ZnO nanoparticles are more effective than Co- ZnO and Co3O4 nanoprticles against all the microorganisms used. The toxicity studies were performed using DAPHTOXKIT F and the 24h EC50 and 48h EC50 were calculated according to the manufactures’ instructions. The results showed that Co- ZnO nanoparticles is less toxic to Daphnia magna compared to ZnO and Co3O4 NPs.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nanoparticles; Antimicrobial activity; Reactive oxygen species; Dissertations, Academic -- South Africa.; Nanoparticles.; Active oxygen.; Nanostructured materials.; Waterborne infections.